Performance of broilers fed with maize colonized by either toxigenic or atoxigenic strains of Aspergillus flavus with and without an aflatoxin-sequestering agent - Aikore, M.O.S.; Ortega Beltran, A.; Eruvbetine, D.; Atehnkeng, J.; Falade, Titilayo D.O.; Cotty, P.J.; Bandyopadhyay, Ranajit (MDPI, 2019)
In warm agricultural areas across the globe, maize, groundnut, and other crops become frequently contaminated with aflatoxins produced primarily by the fungus Aspergillus flavus. Crop contamination with those highly toxic and carcinogenic compounds impacts both human and animal health, as well as the income of farmers and trade. In Nigeria, poultry productivity is hindered by high prevalence of aflatoxins in feeds. A practical solution to decrease crop aflatoxin content is to use aflatoxin biocontrol products based on non-toxin-producing strains of A. flavus. The biocontrol product Aflasafe® was registered in 2014 for use in maize and groundnut grown in Nigeria. Its use allows the production of aflatoxin-safe maize and groundnut. A portion of the maize treated with Aflasafe in Nigeria is being used to manufacture feeds used by the poultry industry, and productivity is improving. One of the conditions to register Aflasafe with the national regulator was to demonstrate both the safety of Aflasafe-treated maize to avian species and the impact of Aflasafe as a public good. Results presented here demonstrate that the use of maize colonized by an atoxigenic strain of Aflasafe resulted in superior (p < 0.05) broiler performance in all evaluated parameters in comparison to broilers fed with toxigenic maize. Use of an aflatoxin-sequestering agent (ASA) was not sufficient to counteract the harmful effects of aflatoxins. Both the safety and public good value of Aflasafe were demonstrated during our study. In Nigeria, the availability of aflatoxin-safe crops as a result of using Aflasafe allows poultry producers to improve their productivity, their income, and the health of consumers of poultry products.